Effect of the manufacturing process on Fiore Sardo PDO cheese microstructure by multi-frequency NMR relaxometry. (February 2021) - Anedda, R.; Pardu, A.; Korb, J.-P.; Curti, E.
Graphical abstract: Highlights: Commercial artisanal and industrial Fiore Sardo cheeses are compared. A proficiency test of NMR relaxometry (20 MHz) was carried out in five laboratories. The two productions exhibited a different molecular mobility. Fast Field Cycling NMR (0.01–10 MHz) describes details of cheese microstructure. Multi-frequency NMR relaxometry discriminates cheese production chains. Abstract: The quality of Fiore Sardo cheese, a traditional Italian dairy product, was analyzed by means of Multi-frequency Nuclear Magnetic (NMR) relaxometry. Specifically, ten cheese wheels were purchased from different production chains, either industrial (N = 5) or artisanal (N = 5) samples. The former came from large scale productions and the latter were produced by shepherds in small quantities and in very small dairy factories. A preliminary interlaboratory proficiency testing of Time Domain - NMR (TD-NMR, 20 MHz) relaxometry by five laboratories, consistently showed that product quality is significantly different in terms of molecular mobility according to their production chain (i.e. industrial or artisanal). More detailed information about cheese microstructure was obtained by Multi-frequency Fast Field Cycling NMR (FFC-NMR) at lower magnetic fields (0.01–10 MHz). According to the interpretative model adopted to describe FFC-NMR data, industrially processed cheeses showed a higher para-casein hydration, higher protein protons to water protons ratio and a higher disorder (lower fractal dimension df ) than artisanal products. It is suggested that differences between artisanal and industrial cheeses generate from the processing steps preceding cheese maturation, and are clearly reflected in the visual appearance of cheeses. This study shows that NMR relaxometry techniques can successfully discriminate Fiore Sardo cheese from different production chains, and paves the way for their implementation in quality control practices of dairy products.